Bibliometric Analyses of Physical and Occupational Therapy Faculty across Canada Indicate Productivity and Impact of Rehabilitation Research. - MacDermid, Joy C.; Fung, Eunice H.; Law, Mary (Physiotherapy Canada, 2015)
Purpose: This study examines physical and occupational therapy faculty across Canada, using bibliometrics and federal funding as indicators of academic impact, and considers the validity of various bibliometric indices. Methods: Faculty members were identified and their rank, professional designation, and department obtained from faculty Web sites. Bibliometric indicators were determined using Publish or Perish software. An independent author (not a faculty member) inspected the data to remove any incorrectly attributed publications. The h-index, citation years, g-index, and total number of citations for each faculty member were retrieved. The Canadian Institutes of Health Research (CIHR) funding database was used to determine the amount of research funding provided to each faculty member as a principal investigator (PI) and his or her total CIHR funding received. Mean faculty indicators by university, rank, gender, and profession were determined. Analysis of variance (ANOVA) was used to detect differences by rank and gender, and measures of association (Pearson correlation coefficients and multiple regression) were used to identify factors that affected h-index and PI funding received. Results: A total of 347 physical and occupational therapy faculty were identified. The median h-index was 5 (inter-quartile range [IQR] 2-8) for assistant professors, 11 (IQR 7-15) for associate professors, and 18 (IQR 12-26) for full professors. ANOVA indicated no significant differences between male and female faculty in terms of h-index or funding received. Regression analysis indicated that 58% of h-index variance could be explained by gender (p=0.039), appointment within a department that provides a (rehabilitation science) PhD programme (p<0.001), rank (p<0.001), CIHR PI funding (p=0.001), or total CIHR funding (p<0.001). Significant predictors of the amount of CIHR funding received as a PI included h-index (p<0.001) and total number of citations (p=0.023), which together explained 27% of the variation in funding received. Conclusion: The h-index, although not without flaws, provides a useful metric that indicates that physical and occupational faculty in Canada are productive scientists having a measurable impact and that this impact increases with rank and greater funding.